2021
DOI: 10.3389/feart.2021.681071
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Distribution of Supra-Glacial Ponds and Ice Cliffs on Verde Glacier, Chile

Abstract: Known for their important role in locally enhancing surface melt, supraglacial ponds and ice cliffs are common features on debris-covered glaciers. We use high resolution satellite imagery to describe pond-cliff systems and surface velocity on Verde debris-covered glacier, Monte Tronador, and Southern Chile. Ponds and ice cliffs represent up to 0.4 and 2.7% of the glacier debris-covered area, respectively. Through the analyzed period and the available data, we found a seasonality in the number of detected pond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…While models accurately simulate the energy and mass balance contribution of individual ice cliffs (Buri et al., 2016; Kneib et al., 2022), their application at large spatial scales is limited by our understanding of the controls of ice cliff distribution. Indeed, estimates of ice cliff density are difficult to make (Anderson, Armstrong, Anderson, & Buri, 2021; Herreid & Pellicciotti, 2018; Kneib et al., 2020) and vary widely in time and space, between 1% and 15% of the debris‐covered area (e.g., Falaschi et al., 2021; Kneib et al., 2021; Loriaux & Ruiz, 2021; Sato et al., 2021; Steiner et al., 2019; Watson, Quincey, Smith, et al., 2017). Remote sensing studies have shown that cliffs are often associated with ponds (Steiner et al., 2019; Watson, Quincey, Carrivick, & Smith, 2017), hinting at a preferential location of ice cliffs where lower glacier longitudinal gradient and surface velocities promote surface ponding (Bolch et al., 2008; Quincey & Glasser, 2009; Quincey et al., 2007; Racoviteanu et al., 2021; Reynolds, 2000; Sakai & Fujita, 2010; Salerno et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…While models accurately simulate the energy and mass balance contribution of individual ice cliffs (Buri et al., 2016; Kneib et al., 2022), their application at large spatial scales is limited by our understanding of the controls of ice cliff distribution. Indeed, estimates of ice cliff density are difficult to make (Anderson, Armstrong, Anderson, & Buri, 2021; Herreid & Pellicciotti, 2018; Kneib et al., 2020) and vary widely in time and space, between 1% and 15% of the debris‐covered area (e.g., Falaschi et al., 2021; Kneib et al., 2021; Loriaux & Ruiz, 2021; Sato et al., 2021; Steiner et al., 2019; Watson, Quincey, Smith, et al., 2017). Remote sensing studies have shown that cliffs are often associated with ponds (Steiner et al., 2019; Watson, Quincey, Carrivick, & Smith, 2017), hinting at a preferential location of ice cliffs where lower glacier longitudinal gradient and surface velocities promote surface ponding (Bolch et al., 2008; Quincey & Glasser, 2009; Quincey et al., 2007; Racoviteanu et al., 2021; Reynolds, 2000; Sakai & Fujita, 2010; Salerno et al., 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most important of these processes include within‐debris convection, meltwater pooling, within‐debris refreezing of meltwater, within‐debris water retention, as well as the presence of ice slopes and cliffs (Petersen et al., 2022; Reid & Brock, 2010). The presence of supraglacial water bodies, bare‐ice slopes and ice cliffs has been shown to potentially increase local melt rates substantially and act as local ablation hotspots (Buri et al., 2021; Loriaux & Ruiz, 2021; Miles et al., 2022). To capture such small‐scaled and detailed processes, however, high resolution input data are required at both temporal and spatial scales, which is out of scope for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Their aspect can vary widely within a single cliff and between different cliffs on a single glacier (Steiner and others, 2019). Ice cliffs cover , 15% of the area of the debris-covered tongue of glaciers (Steiner and others, 2019;Anderson and others, 2021;Kneib and others, 2021a;Loriaux and Ruiz, 2021). Their genesis has been hypothesized to be related to spatially heterogeneous debris thicknesses leading to differential melt and debris mobilization (Nicholson and others, 2018;Moore, 2021), subglacial streams or ponds leading to debris remobilization and undercutting (Sakai and others, 2000;Mölg and others, 2019), collapsing englacial channels (Benn and others, 2012;Reid and Brock, 2014) or crevasses (Reid and Brock, 2014;Steiner and others, 2019).…”
Section: Morphology and Ice Dynamicsmentioning
confidence: 99%
“…Complex models have only been applied in recent years (Buri and others, 2016b), along with the investigation of their distribution beyond the glacier scale (Steiner and others, 2019;Kneib and others, 2021a). More recently, they have also been described in the Alps (Reid and Brock, 2014), Andes (Loriaux and Ruiz, 2021) and Alaska Range (Anderson and others, 2021).…”
Section: Introductionmentioning
confidence: 99%